Geometric solution of problems involving irrationality - Madrakhimov T. (Periodica Journal, 2023)
This article presents the solutions of some Olympiad problems on the topic of triangles, which are not often encountered. Through these, the student learns that he can solve Olympiad problems not in the same way, but also through different creative thinking
Keywords: Triangle; inequality; proof